Dispute Resolution in Marriage Customs: Cultural and Sharia Approaches in the Malakok Tradition in Minangkabau - Putri, Wahyuni; Zulkifli, Zulkifli; Effendi, Amri (JISRAH: Jurnal Integrasi Ilmu Syariah, 2024)
The main issue in this thesis is to explain the resolution of marital conflicts among non-malacok couples in Nagari Bungo Tanjuang. This field research aims to understand and describe the process of conflict resolution and the impacts of such resolutions in marital conflicts among non-malacok couples in Nagari Bungo Tanjuang. The findings of this research indicate that the forms of marital conflicts among non-malacok couples in Nagari Bungo Tanjuang include visible conflicts such as economic factors, differences in opinions, lack of mutual respect, interference from in-laws, and domestic violence. The reason they do not engage in malacok is due to the high adat costs, amounting to 3,000,000 IDR, which only covers the adat money; further costs will follow for the malacok process. The resolution method employed is non-litigation, using family-based and customary approaches. The impact of this resolution, however, is the dissatisfaction among the conflicting parties, as no peaceful resolution was achieved as expected, which further worsens the relationship, leading to separation, either through living apart or an informal divorce. This situation negatively affects the obligations between husband and wife as well as the children. Despite the application of several resolution models in the marital conflicts, the conflicts did not result in a satisfactory solution, thus not ensuring the resilience of the marriage.